Aerobic fitness evaluation during walking tests identifies the maximal lactate steady state - Puga, Guilherme Morais [UNESP]; Kokubun, Eduardo [UNESP]; Simões, Herbert Gustavo; Nakamura, Fabio Yuzo; Campbell, Carmen Sílvia Grubert (Hindawi, 2012)
Objective. The aim of this study was to verify the possibility of lactate minimum (LM) determination during a walking test and the validity of such LM protocol on predicting the maximal lactate steady-state (MLSS) intensity. Design. Eleven healthy subjects (24.2 ± 4.5 yr; 74.3 ± 7.7 kg; 176.9 ± 4.1 cm) performed LM tests on a treadmill, consisting of walking at 5.5 km h -1 and with 20-22% of inclination until voluntary exhaustion to induce metabolic acidosis. After 7 minutes of recovery the participants performed an incremental test starting at 7% incline with increments of 2% at each 3 minutes until exhaustion. A polynomial modeling approach (LMp) and a visual inspection (LMv) were used to identify the LM as the exercise intensity associated to the lowest [bLac] during the test. Participants also underwent to 24 constant intensity tests of 30 minutes to determine the MLSS intensity. Results. There were no differences among LMv (12.6 ± 1.7 %), LMp (13.1 ± 1.5 %), and MLSS (13.6 ± 2.1 %) and the Bland and Altman plots evidenced acceptable agreement between them. Conclusion. It was possible to identify the LM during walking tests with intensity imposed by treadmill inclination, and it seemed to be valid on identifying the exercise intensity associated to the MLSS. Copyright © 2012 Guilherme Morais Puga et al.
Keywords: lactic acid; lactic acid derivative; adult; exercise intensity; female; human; human experiment; lactate minimum; male; maximal lactate steady state; metabolic acidosis; metabolic parameters; normal human; steady state; treadmill ergometry; walking; aerobic metabolism; blood; reference value; Adult; Aerobiosis; Humans; Lactates; Male; Reference Values; Walking